Impact of Irrigation of Distillery Spentwash on the Nutrients of Herbal Medicinal Plants - Chandraju, S.; Nagendraswamy, R.; Nagendraswamy, Girija; Chidankumar, C.S. (Asian Journal of Chemistry, 2010)
Cultivation of some herbal medicinal plants was made by irrigation with distillery spent wash of different concentrations. The spent wash i.e., primary treated spent wash, 33 and 50 % spent wash were analyzed for their plant nutrients such as nitrogen, phosphorous, potassium and other physical and chemical characteristics. Experimental soil was tested for its chemical and physical parameters. Seeds of herbal medicinal plants were sowed in the prepared land and irrigated with raw water, 33 and 50 % spent wash. The impact of distillery spent wash on proximate principles (moisture, protein, fat, fibre, carbohydrate, calcium, phosphorous, iron and energy), vitamin content (carotene and vitamin-C), mineral and trace elements (magnesium, sodium, potassium, copper, manganese, zinc, chromium and nickel) of herbal medicinal plants were investigated. It was found that the uptake of nutrients of all herbal medicinal plants in case of 33 % spent wash irrigation when compared with 50 % spentwash and raw water irrigations.